2004
DOI: 10.1111/j.1462-8902.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the human β1,β2‐ and β3‐adrenergic receptor genes are not associated with morbid obesity in children and adolescents

Abstract: We did not detect significant differences for allele and carrier frequencies of individual polymorphisms. Together with previously obtained data on genotype distribution of a beta(3)-AR variant in the same study group, no significant differences were found between obese and lean subjects for the distribution of individuals with variants in none, one, two or all three beta-ARs. Our data make it unlikely that polymorphisms in beta-ARs are involved in the pathogenesis of early onset obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
3
22
2
2
Order By: Relevance
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
“…Several of these failed to identify any association [3][4][5][6][7][8][9]. Other studies have found significant associations [8,10,11], but without a consensus regarding which allele is associated with obesity or related traits.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is some evidence to suggest that polymorphisms on the beta-2 adrenergic receptor, expressed mainly in subcutaneous adipose tissue, may also be linked to variation in BMI and obesity related phenotypes. Thus, the Arg16Glyn variant of ADRB2 has been associated with signifi cant weight gain in childhood through to young adults (Angeli et al, 2011;Ellsworth et al, 2002;Lagou et al, 2011) though data are mixed Tafel et al, 2004). This variant appears to act synergistically with the LEPR Gln223Arg SNP for risk of obesity (Angeli et al, 2011) and may moderate (ameliorate) the effect on adiposity by increased vigorous activity .…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%
“…2,6,7 Two candidate genes, lipoprotein lipase (LPL) gene and b1-adrenergic receptor (ADRB1) gene are considered potentially important to obesity. [8][9][10][11][12][13][14][15][16] Lipoprotein lipase as a lypolytic enzyme plays an important role in catabolism of triglycerides of chylomicrons and very low-density lipoproteins and deposition of fatty acids in adipose tissue. 17 The Ser447Stop polymorphism of LPL gene located in exon 9 produces a truncated protein without Ser-Gly dipeptide in the COOHterminus that has been associated with a favorable lipid profile.…”
mentioning
confidence: 99%
“…21,22 However, this polymorphism alone has not been associated with obesity. [14][15][16] Since adrenoreceptors and LPL are involved in pathways of lipid and energy metabolism, it has been suggested that interactions between these genes could have effect on obesity. 9,12 However, there is a paucity of information regarding the interaction effect between Ser447Stop variant of the LPL gene and Arg389Gly variant of the ADRB1 gene on obesity, especially on the development of obesity from childhood to adulthood.…”
mentioning
confidence: 99%